KEPEMIMPINAN DAN KEPRAMUGARIAN AKUNTANSI PADA UNIVERSITAS ISLAM “45” BEKASI - S. Djoko Sambodo; Diana Fajarwati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2006)
One of the most important determinants of manajerial effectiveness for a leader is success in organizing and influencing subordinates for keeping institution ( or office ) assets. The present research examine the correlations between leadership and operative accounting in Universitas Islam “ 45 “ Bekasi with the sample consisted of 17 leaders and 40 accounting/finance staffs. This research find aut that 0,109 correlation coefficient (r). This study also conclude that there is a weak correlation between leadership and operative accounting.